The Role of Creativity, Product Quality, and Innovation in Enhancing MSME Competitive Advantage - Yanita Eella Nilla Chandra; Salsabila Farhana Andriani; Imas Chandra Pratiwi; Ratri Kurniasari (Jurnal Manajemen dan Kewirausahaan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) operating in the food and beverage (F&B) sector in Depok City face increasing competitive pressures in a rapidly evolving market environment. Despite their significant contribution to local economic development, many F&B MSMEs continue to encounter challenges related to limited creativity, inconsistent product quality, and insufficient product innovation, which may constrain the development of sustainable competitive advantage. The aim of this study is to investigate the effects of creativity and product quality on competitive advantage, with product innovation serving as a mediating variable. A quantitative explanatory research design was employed, involving 200 F&B MSMEs owners in Depok City, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that both creativity and product quality positively and significantly influence product innovation. Product innovation, in turn, has a significant positive effect on competitive advantage. Furthermore, product innovation mediates the relationship between creativity and competitive advantage, as well as the relationship between product quality and competitive advantage. These findings underscore the critical role of product innovation in translating organizational capabilities into sustainable competitive advantage.